COMPUTER ASSISTED DRAWING IN THE FACULTY OF INDUSTRIAL ENGINEERING - UNMSM - Rojas Lazo, Oswaldo (2005)
In engineering a great deal of the design process is based in graphics, their knowledge and management being important for students' professional training . Over the last years, technologies arising from drawing and design are constantly innovating. For this reason the adoption and application of the (CAD/CAM) technology in the curricula will allow to train the future industrial engineers better.